Respostas
respondido por:
1
.
Ola evelyn
x + y = 9
x - y = 5 (adição)
2x = 14
x = 7
7 + y = 9
y = 2
.
Ola evelyn
x + y = 9
x - y = 5 (adição)
2x = 14
x = 7
7 + y = 9
y = 2
.
evelyn161:
oi muito obrigada
respondido por:
0
Isole os Xs de ambas as expressões: x = 9 - y / x = 5 + y
x =x => 9 - y = 5 + y => y + y = 9 - 5 => 2y = 4 => y = 4/2 = /// y = 2 ///
x =x => 9 - y = 5 + y => y + y = 9 - 5 => 2y = 4 => y = 4/2 = /// y = 2 ///
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás